Kinetic Study of Crystal Violet Dye Adsorption from Wastewater Using Populus nigra Leaf Powder - Fatima Anwer; Ammara Nazir (Journal of Basic and Emerging Sciences, 2025)
This study investigates the potential of Populus nigra (black poplar) leaf powder as a low-cost, eco-friendly adsorbent for the removal of Crystal Violet dye from wastewater. Batch adsorption experiments were conducted to assess the effects of pH, contact time, adsorbent dosage, initial dye concentration, and temperature. Optimal removal conditions were observed at pH 10 and 15 °C, achieving an adsorption efficiency of 84%. The adsorption followed the Langmuir isotherm model (R² = 0.9696), indicating monolayer adsorption, and the kinetics fit the pseudo-second-order model (R² = 1), suggesting chemisorption as the rate-limiting step. These results highlight Populus nigra leaves as a sustainable biosorbent capable of reducing dye pollution in industrial effluents, offering a promising alternative to conventional treatment methods